Преобразование характеристик вынужденных колебаний в электронных приборах О-типа мм диапазона - Одаренко, Е. Н.; Шматько, А. А. (ХНУРЭ, 2002)
The regularities of physical processes in the on-line nonlinear millimeter waves oscillatory systems with different kinds of external action are researched. The effect of space allocation parameters of the non-uniform focusing field on the characteristics of the forced oscillations in modes of stationary and non-stationary oscillations is considered. The regularities of resonance characteristics conversion for different levels of external parametric action are researched.
Keywords: приборы О-типа; мм диапазон; вынужденные колебания; синхронизация